2008
DOI: 10.1002/ibd.20502
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant innate immune responses in TLR-ligand activated HLA-B27 transgenic rat cells

Abstract: HLA-B27 TG rats have an aberrant cell composition, altered functional TLR expression, and an intrinsic defect in IL-10 production in response to TLR ligands, which may result in exaggerated proinflammatory responses to commensal enteric bacteria and uncontrolled inflammation in this colitis model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…An incidental but consistent finding was that, when compared with age-matched controls, the splenocytes from B27-TG rats had consistently higher proportions of granulocytes, the majority of which were CD11b. An enhanced granulocytic infiltrate has been observed macroscopically in the gastrointestinal (GI) tract of B27-TG rats,23 while a second study has reported that B27-TG rat spleens contain a higher proportion of CD11b cells compared with control littermates 24. It is unclear whether CD11b granulocytes merely represent ongoing inflammation or play a pathogenic role, perhaps through an expression of innate immune receptors, such as PIR, which can interact with NC-B27.…”
Section: Discussionmentioning
confidence: 99%
“…An incidental but consistent finding was that, when compared with age-matched controls, the splenocytes from B27-TG rats had consistently higher proportions of granulocytes, the majority of which were CD11b. An enhanced granulocytic infiltrate has been observed macroscopically in the gastrointestinal (GI) tract of B27-TG rats,23 while a second study has reported that B27-TG rat spleens contain a higher proportion of CD11b cells compared with control littermates 24. It is unclear whether CD11b granulocytes merely represent ongoing inflammation or play a pathogenic role, perhaps through an expression of innate immune receptors, such as PIR, which can interact with NC-B27.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in several systems, including B27/Hu␤ 2 m-transgenic rats, that B27 heavy chains have an unusual tendency to misfold and form homodimers and higher oligomers (21,(34)(35)(36). This misfolding can induce an unfolded protein response that can synergize with innate immune signals in the activation of a proinflammatory cytokine response (37), and other aberrant innate responses have also been documented (38). Our findings are also consistent with data from human and murine systems suggesting recognition of HLA-B27 by CD4ϩ T cells (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in several systems, including B27/Huβ 2 m‐transgenic rats, that B27 heavy chains have an unusual tendency to misfold and form homodimers and higher oligomers (21, 34–36). This misfolding can induce an unfolded protein response that can synergize with innate immune signals in the activation of a proinflammatory cytokine response (37), and other aberrant innate responses have also been documented (38). Our findings are also consistent with data from human and murine systems suggesting recognition of HLA–B27 by CD4+ T cells (39, 40).…”
Section: Discussionmentioning
confidence: 99%